Critical Discourse Analysis Related to Power Relation in Film â€œThe Judgeâ€ - Ahmad Cholilir Rozzaq; Dwijani Ratnadewi (Tell : Teaching of English Language and Literature Journal, 2016)
The researcher analyzed power relation in film â€œThe Judgeâ€ by using theory of CDA in interpreting hidden meaning of words. CDA was a theory that study about the relation between the social life and talk in interaction. The approach of this research was CDAâ€™s van Dijk as it became the most appropriate theory to analyze since grammar, metaphor, intonation, social cognition and societal structures were included. In this research, descriptive qualitative was applied to analyze the data. â€œThe Judgeâ€ film script was used as the source of data. The researcher focused on the main characterâ€™s words which contain power in the social relation especially in court. Some powers had been found in this research, there were power as control and threat that main characters used in building their conversation. In this research, main characters used power in the community because they wanted to dominate the conversation.